Comparison of Outcomes of Open versus Laparoscopic Hysterectomy at a Tertiary Care Military Hospital - Qurat-ul-Ain (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the outcomes of open versus laparoscopic hysterectomy in women at a tertiary care military hospital.Study Design: Prospective comparative study.Place and Duration of Study: Department of Gynecology, Combined Military Hospital, Lahore Pakistan, from Jul 2021 to Jun 2023.Methodology: All patients who were advised to undergo hysterectomy for any gynecological reason at our teaching unit were recruited for this study. They were divided into two groups via block randomization. Group I underwent laparoscopic hysterectomy, while Group II underwent open hysterectomy. Clinical parameters such as operative time, blood loss, and fall in hemoglobin, postoperative pain, and hospital stay were compared between the two groups.Results: Out of 618 women recruited, 64(10.4%) were premenopausal, 242(39.2%) were peri menopausal, and 312(50.5%) were postmenopausal. The mean age of the study participants was 50.14±8.48 years. Mean blood loss (p-value =0.011), mean fall in hemoglobin (p-value